Daya hasil beberapa galur harapan jagung pulut lokal Papua Barat - Nouke Lenda Mawikere; Alce I. Noya; Amelia S. Sarungallo; Imam Widodo; F.H. Listyorini; Lenci E.K. Rumbewas; Musina H. Kurni (Program Pascasarjana Universitas Papua, 2023)
The potential lines of West Papua local waxy corn has been already obtained in the previous studies, but the yields have not been further tested. In seed certification for the release of varieties from plant breeding results, it is necessary to conduct multilocation tests to obtain stable and superior yields in various locations. The aim of this research is to test the continued yield of potential lines of West Papua's local waxy corn at several areas in West Papua Province. The study was conducted in Prafi and West Manokwari Districts. The method used was an observational method using a Randomized Complete Block Design of 2 factors: Factor 1 was treatment of 7 local corn genotypes and factor 2 was treatment of 2 locations. Each treatment was repeated 3 times. Variables were observed included yield components of the maize genotypes tested. The data obtained were analyzed using ANOVA and if it had a significant effect, further BNJ test was performed at 95% confidence level. The results showed that productivity (seed weight ha-1) of the 7 genotypes tested were: 1) Ranging from 2.72 tons ha-1 (KM-BC3F1) to 7.66 tons ha-1 (AM-BC3F1 ) in the Prafi District, 2) from 3.30 tons ha-1 (AP-BC3F1) to 7.46 tons ha-1 (KL) in the West Manokwari District, and 3) from 3.28 tons ha-1 (KM-BC3F1) to 5.92 tons ha-1 (AM-BC3F1) in the G x L interactions. Genotype AM-BC3F1, AP-BC3F1, and P have higher productivity in Prafi District, on the contrary genotype KM-BC3F1, KP-BC3F1, AL, and KL have higher productivity in West Manokwari District.